Evaluasi Kerusakan Fisik Pohon dalam Upaya Menghadirkan Pohon Jalur Hijau yang Aman di Kota Padang - Sherly Arisanti; Bambang Sulistyantara; Nizar Nasrullah (http://arl.faperta.ipb.ac.id/, 2022)
The existence of trees in the landscape has an important role to create the comfort for users. The physical condition of the tree is something that needs to be considered in maintaining the comfort of road users. Poor tree conditions is possibly endanger road users if in the rainy season with high rainfall intensity and strong winds which possible cause tree branches to break and trees fall. The purpose of this study is to identify the physical damage of trees and to propose a recommendation for handling them on the green lane. The research was conducted on 3 green lanes, namely Khatib Sulaiman street, Rasuna Said street and Ujung Gurun street in Padang City. The method used refers to the FHM (USDA Forest Health Monitoring) method using the damage index that has been determined by the USDA Forest Service. Based on the results of the study, there were 1,108 trees that were damaged. The location of the most damage occurred on the lower stem of 32.9%, branching in the crown of 20.4% and buds and shoots of 19.8%. There were 11 types of damage that occurred with the most damage, namely open wounds by 32.4%, dead ends by 20.1% and broken or dead branches by 18.1%. The three type of damages are dominated by healthy and moderately damaged trees. Damage handling is done physically and chemically.